2019
DOI: 10.1063/1.5086912
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic linearized Navier-Stokes equation on describing the effect of surface roughness on hypersonic boundary-layer transition

Abstract: Laminar-turbulent transition is crucially influenced by wall roughness. This paper develops a numerical approach based on the harmonic linearized Navier-Stokes (HLNS) equations to accommodate the scattering effect of the rapidly distorted mean flow induced by a two-dimensional hump or indentation at the wall on the oncoming instability modes (including the Mack first and second modes) in a hypersonic boundary layer. Due to the ellipticity of the scattering system when the roughness width is comparable with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Computational and theoretical studies have also examined the influence of roughness on high-speed boundary-layer stability (Duan, Wang & Zhong 2010;Marxen et al 2010;Riley et al 2014;Groskopf & Kloker 2016;Zhao et al 2019;Dong & Zhao 2021;Haley & Zhong 2023). We first consider the impact of 2-D modifications of the surface.…”
Section: Effects Of Roughness On Transition To Turbulencementioning
confidence: 99%
See 3 more Smart Citations
“…Computational and theoretical studies have also examined the influence of roughness on high-speed boundary-layer stability (Duan, Wang & Zhong 2010;Marxen et al 2010;Riley et al 2014;Groskopf & Kloker 2016;Zhao et al 2019;Dong & Zhao 2021;Haley & Zhong 2023). We first consider the impact of 2-D modifications of the surface.…”
Section: Effects Of Roughness On Transition To Turbulencementioning
confidence: 99%
“…However, placement near the trailing edge enhanced stability. Most recently, Zhao et al (2019) used the harmonic linearized Navier-Stokes equations to evaluate the effect of a 2-D hump or indentation on a flat wall on boundary-layer stability. They confirmed that the synchronization points of the instability waves are critical modulators of the impact of roughness.…”
Section: Effects Of Roughness On Transition To Turbulencementioning
confidence: 99%
See 2 more Smart Citations
“…where δ 99 = 8.7 denotes the nominal boundary-layer thickness at x = x 0 and J = 580. Such an allocation ensures that half of the total grid points are allocated to the boundary layer, which has also been used in our previous work (Zhao, Dong & Yang 2019;Song et al 2022).…”
Section: Nonlinear Evolution Of the Boundary-layer Perturbationsmentioning
confidence: 99%